The Managerial and Government Ownership Effect on Dividend Policy: The Moderating Role of Investment Opportunities - Abdul Fatah Ismail; Nadia Anridho (Universitas Negeri Semarang, 2024)
Purpose: This study investigates agency conflicts related to dividend policy within corporate companies, focusing on managerial ownership and government ownership. Methods: Using a quantitative approach, the study employs multiple linear regression and moderation regression analyses. Data from 89 observations of State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange from 2015 to 2019 are analyzed to examine the relationships between ownership structures and dividend policy, and the moderating role of investment opportunities. Results: The findings indicate that managerial ownership negatively influences dividend policy, with investment opportunities failing to moderate this negative effect. Conversely, government ownership positively impacts dividend policy, but investment opportunities weaken this positive effect. These results underscore the distinct impacts of managerial and government ownership on dividend policies within SOEs. Novelty: This research offers new insights into agency conflicts and dividend policies of SOEs, a less explored area in corporate finance. It highlights the moderating role of investment opportunities, adding a unique perspective to the understanding of these relationships. However, the study is limited by its sample size, focusing only on publicly listed SOEs, while most SOEs have not gone public. Further research is necessary to fully understand agency conflicts in corporate financial relations across a broader range of SOEs.